2010
DOI: 10.1007/s11202-010-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

C*-algebras generated by cancellative semigroups

Abstract: A C * -algebra generated by a commuting family of isometries is a natural generalization of the Toeplitz algebra. We study the * -automorphisms and invariant ideals of the C * -algebra generated by a semigroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In [5,6] it is shown that the mapping A → A, A = A(1), generates an isomorphism between the C * -algebras T and T . Analogous results for a more general case were obtained in [7]. Thus, the representation σ :…”
Section: Toeplitz Algebra's Subslagebras Fixed Relative To Finite Grsupporting
confidence: 72%
“…In [5,6] it is shown that the mapping A → A, A = A(1), generates an isomorphism between the C * -algebras T and T . Analogous results for a more general case were obtained in [7]. Thus, the representation σ :…”
Section: Toeplitz Algebra's Subslagebras Fixed Relative To Finite Grsupporting
confidence: 72%
“…We have studied earlier the C * -algebras generated by representations of ordered semigroups [7,8,9,10,11,12]. The present paper is a continuation of the study begun in the article [13].…”
Section: Introductionmentioning
confidence: 89%
“…We say that the isometric representation π : S → B(H π ) is an inverse representation if S * π is an inverse semigroup under the operation of *involution, or equialently, the semigroup S * 0,π is a semigroup of idempotents in S * π , that is, the semigroup of orthogonal projections. According to the Lemma 2.2 in [5] every semigroup S has at least one inverse representation. On the other hand if the defined above order on S is a total order, then all the isometric representations of the semigroup S are inverse (see [1]).…”
Section: Lemma 22mentioning
confidence: 99%